2003
DOI: 10.1002/ccd.10710
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery stenting using distal emboli protection and transcranial Doppler

Abstract: Recent studies have shown the feasibility and safety of the percutaneous approach for the treatment of vertebrobasilar disease using either balloon angioplasty alone, coronary stents, or combined angioplasty followed by stenting. The major concern in performing percutaneous procedures for the treatment of obstructive disease of the vertebrobasilar circulation involves the risk of embolic phenomena. We describe the successful treatment of a symptomatic patient with bilateral vertebrobasilar disease utilizing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…However, embolic complications were described in these series, as distal protection devices were not utilized. There has been a single previous case report of distal protection embolic filter used in vertebral artery stenting with a bare metal stent with good results (10). Embolic distal protection devices are routinely employed in carotid artery stenting.…”
Section: Discussionmentioning
confidence: 99%
“…However, embolic complications were described in these series, as distal protection devices were not utilized. There has been a single previous case report of distal protection embolic filter used in vertebral artery stenting with a bare metal stent with good results (10). Embolic distal protection devices are routinely employed in carotid artery stenting.…”
Section: Discussionmentioning
confidence: 99%
“…The use of EPDs has been described in several studies involving angioplasty and stenting of lesions of a VA origin [1,5,7,9,10,12,13,14]. To date, newer or alternative methods for cerebral protection for the treatment of vertebrobasilar (VB) stenosis have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the evidentiary support for protection devices in the treatment of carotid artery lesions, EPD use has translated into percutaneous interventions of proximal vertebral artery (VA) stenosis [9,12]. Lesions of a VA origin and at the V1 segment lend themselves well for distal embolic protection as vessel size approximates the coronaries; there are several devices available for use.…”
Section: Introductionmentioning
confidence: 99%
“…29 There were a few anecdotal case reports regarding the protection technique in recanalization of a V1 occlusion by use of a flow-reversal technique 30,31 or a distal filter protection device. 32 Our clinical experience has shown that smooth passage of a 0.035-inch guidewire could be followed by the introduction of a 4F angiocatheter, which allows clot aspiration and also accepts a distal balloon system with a 0.014-inch outer diameter. A more rigid microguidewire can also be used for probing the occluded segment.…”
Section: Discussionmentioning
confidence: 99%